Critical reasoning : a practical introduction - Thomson, Anne (Routledge, 1996)
Reasoning is the everyday process that we all use in order to draw conclusions from facts or evidence. To think critically about what you read and hear is a vital skill for everyone, whether you are a student or not. When we are faced with texts, news items or speeches, what is being said is often obscured by the words used and we may be unsure whether our reasoning, or that of others, is in fact sound. By the end of this topical and exercise-based introduction to critical thinking, you will be able to: * identify flaws in arguments * analyse the reasoning in newspaper articles, books or speeches * approach any topic with the ability to reason clearly and to think critically This stimulating new introduction to reasoning will appeal to all those who would like to improve their reasoning skills, whether at work, in class or in the seminar.